Preoperative prealbumin level as an independent predictor of long-term prognosis after liver resection for hepatocellular carcinoma: a multi-institutional study. Issue 2 (February 2019) - Li, Ju-Dong; Xu, Xin-Fei; Han, Jun; Wu, Han; Xing, Hao; Li, Chao; Yu, Jiong-Jie; Zhou, Ya-Hao; Gu, Wei-Min; Wang, Hong; Chen, Ting-Hao; Zeng, Yong-Yi; et al.
Abstract: Background: Serum prealbumin is a sensitive and stable marker for nutritional status and liver function. Whether preoperative prealbumin level is associated with long-term prognosis in patients undergoing liver resection for hepatocellular carcinoma (HCC) is unclear. Methods: Patients who underwent liver resection for HCC between 2001 and 2014 at six institutions were enrolled. These patients were divided into the low and normal prealbumin groups using a cut-off value of 170 mg/L for preoperative prealbumin level. The overall survival (OS) and recurrence-free survival (RFS) were compared between them. Results: In 1483 patients, 437 (29%) had a low prealbumin level. The 3- and 5-year OS and RFS rates of patients in the low-prealbumin group were 57 and 31%, and 40 and 20%, respectively, which were significantly poorer than those in the normal-prealbumin group (76 and 43%, and 56 and 28%, respectively, both p < 0.001). Multivariable Cox-regression analyses revealed that preoperative prealbumin level was an independent predictor of OS (HR, 1.45, 95% CI: 1.24–1.70, p <0.001) and RFS (HR, 1.28, 95% CI: 1.10–1.48, p <0.001). Conclusions: Preoperative prealbumin level could be used in predicting long-term prognosis for patients undergoing liver resection for HCC.